1978
DOI: 10.1111/j.1432-1033.1978.tb12751.x
|View full text |Cite
|
Sign up to set email alerts
|

Control of Ornithine Decarboxylase Activity in Physarum by Polyamines

Abstract: The addition of putrescine, spermidine, or spermine, to cultures of Physarum p~I y c e~h a / u m rapidly reduced the activity of ornithine decarboxylase, with maximal inhibition, 80 -90 %, occurring after 90 min. This response was not due to a decrease in enzyme molecules, but rather to the rapid conversion of the active enzyme to a stable, catalytically less active form. This response to exogenous polyamines was not accompanied by the appearance of a macromolecular inhibitor (antizyme) either free, or bound t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0
4

Year Published

1979
1979
1991
1991

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 19 publications
2
22
0
4
Order By: Relevance
“…Several modified forms of the enzyme have been reported, including phosphorylated [7] and transamidated forms [6], and the existence of an equilibrium between active and cryptic forms of ODC has also been suggested [lo]. Moreover, different investigators have observed multiple &forms of ODC after fractionation by gel permeation chromatography [13,17], but the physiological significance of these forms remains unknown.…”
Section: Resultsmentioning
confidence: 99%
“…Several modified forms of the enzyme have been reported, including phosphorylated [7] and transamidated forms [6], and the existence of an equilibrium between active and cryptic forms of ODC has also been suggested [lo]. Moreover, different investigators have observed multiple &forms of ODC after fractionation by gel permeation chromatography [13,17], but the physiological significance of these forms remains unknown.…”
Section: Resultsmentioning
confidence: 99%
“…The data presented here, as well as past studies on Physarum [8] and mammalian cells [ 1,2,11] correlating cell membrane integrity with intracellular ODC activity, suggest that the mechanism interconverting ODC forms may be located at the cell membrane. Furthermore, the inhibition of this osmoticallyinduced activation, but not inactivation, by sodium azide suggests that only the former reaction may be ATP dependent.…”
Section: Discussionmentioning
confidence: 70%
“…In E co&, for example, osmotic shock induces the loss of most cellular putrescine, and uptake of K' from the media, within 5 min [7]. A similar release of cellular polyamines to the media might be sufficient to induce inactivation of ODC in Physarum [8], yet this is not likely as the response time to extracellular polyamines has been shown to be considerably longer than the 4-6 min required for the osmotic effect. Furthermore the reabsorption of the released polyamine would not be fast enough to produce the observed rapid return to initial enzyme activity levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A substantial increase in the intracellular polyamines is observed when extracellular concentrations rise to the endogenous concentrations (Clark & Fuller, 1975;Heller et al, 1978) and furthermore exogenous polyamines appear not to enter the same pool as amines synthesized within the cell (Russell et al, 1970). These findings, together with the observed sensitivity of most cells to exogenous polyamine in the presence of much higher endogenous concentrations (Mitchell et al, 1978;Heller et al, 1978), make it difficult at present to assess the reason for different effects on cyclic AMP of increasing concentrations ofexogenous polyamines. We are tempted to suggest that this phenomenon might be related to a different availability of free and more active polycations inside the cell.…”
Section: Discussionmentioning
confidence: 83%